A curcumin microcapsule with multi-coated metal organic framework and preparation method thereof
By forming a chitosan-sodium alginate coating on the curcumin metal organic framework, the problem of limited application of metal organic framework materials in food and medicine in the prior art is solved, efficient encapsulation and loading of curcumin is achieved, antioxidant and stability are enhanced, and the effect of slow release is achieved.
Patent Information
- Application Number
- CN202410160303.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-02-02
- Publication Date
- 2025-03-28
- Estimated Expiration
- 2044-02-02
AI Technical Summary
The application of existing metal organic framework materials in food and medicines is limited. Due to the high cost, cumbersome preparation, poor water solubility and drug oxidation, the drug effect is especially affected by the solubility and absorption of curcumin, reducing bioavailability and efficacy.
The γ-cyclodextrin metal organic framework was prepared by solvent thermal synthesis, and a chitosan-alginate coating was formed around the curcumin metal organic framework by electrostatic deposition to prepare curcumin microcapsules with multi-coated metal organic framework.
It achieves efficient encapsulation and loading of curcumin, extends the retention rate of curcumin in different media, enhances antioxidant properties and UV irradiation stability, and has the effect of slowly releasing curcumin.
Smart Images

Figure CN118021999B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of microcapsule preparations, and in particular relates to a multi-coated metal organic framework curcumin microcapsule and a preparation method thereof. Background Art
[0002] Curcumin is a fat-soluble natural pigment, which is mainly extracted from the rhizomes or tubers of various ginger plants such as turmeric, turmeric, and zedoary. It is an acidic polyphenol substance, insoluble in water, easily soluble in alcohol and alkaline solutions, and is usually used as a food additive and acid-base indicator. It also has anti-inflammatory, anti-aging, anti-atherosclerotic, anticoagulant, antiviral, fibrosis inhibition, nerve function protection, oxygen free radical elimination, lipid-lowering, blood sugar-lowering, anti-rheumatoid and tumor growth inhibition pharmacological effects.
[0003] Metal organic framework (MOF) is a new type of porous crystalline material formed by self-assembly of metal ions or ion clusters and organic ligands, with advantages such as large specific surface area, easy adsorption and embedding, and easy functionalization. However, common MOF materials are expensive, the preparation process is cumbersome, and the water solubility is poor, which limits their application in food and medicine. When loading drugs, they may cause drug oxidation and affect the efficacy, especially the dissolution and absorption of curcumin, reduce the bioavailability of the drug, and affect the efficacy. Summary of the invention
[0004] The purpose of this section is to summarize some aspects of embodiments of the present invention and briefly introduce some preferred embodiments. Some simplifications or omissions may be made in this section and the specification abstract and the invention title of this application to avoid blurring the purpose of this section, the specification abstract and the invention title, and such simplifications or omissions cannot be used to limit the scope of the present invention.
[0005] In view of the above problems and / or the problems existing in the prior art, the present invention is proposed.
[0006] Therefore, the purpose of the present invention is to overcome the deficiencies in the prior art and provide a method for preparing curcumin microcapsules with a multi-coated metal organic framework.
[0007] In order to solve the above technical problems, the present invention provides the following technical solutions: comprising:
[0008] Dissolving cyclodextrin powder and potassium hydroxide powder in water at a molar ratio of 6 to 9:1, hydrating after refrigeration to obtain a reaction solution;
[0009] Methanol is added to the reaction solution and heated, then a surfactant is added, the solution is cooled and centrifuged, and the solution is washed with methanol and freeze-dried to obtain a metal organic framework powder;
[0010] Adding metal organic framework powder and curcumin powder together into an ethanol solution at a mass ratio of 1:0.7-1.1, washing the precipitate three times with the ethanol solution after centrifugation, and vacuum drying to obtain curcumin metal organic framework powder;
[0011] Adding curcumin metal organic framework powder to chitosan solution and mixing and stirring to obtain a curcumin metal organic framework microcapsule solution coated with chitosan;
[0012] The curcumin metal organic framework microcapsule solution coated with chitosan was added into the polysaccharide solution, and the precipitate was washed three times with an ethanol solution after centrifugation, and the curcumin microcapsules with multiple coating metal organic frameworks were obtained after vacuum drying.
[0013] As a preferred embodiment of the method for preparing the multi-coated metal organic framework curcumin microcapsules of the present invention, the cyclodextrin comprises one of α-cyclodextrin, β-cyclodextrin and γ-cyclodextrin, and the molar ratio of the cyclodextrin to potassium hydroxide is 7 to 8:1.
[0014] As a preferred embodiment of the method for preparing the multi-coated metal organic framework curcumin microcapsules of the present invention, the surfactant comprises one of PEG200, PEG2000, PEG10000 and PEG20000, and the concentration of the surfactant is 2-10 mg / mL.
[0015] As a preferred embodiment of the method for preparing the multi-coated metal organic framework curcumin microcapsules of the present invention, the concentration of the curcumin is 2 to 10 mg / mL.
[0016] As a preferred embodiment of the method for preparing the multi-coated metal organic framework curcumin microcapsules of the present invention, the mass ratio of the curcumin powder to the metal organic framework powder is 0.8 to 1:1.
[0017] As a preferred embodiment of the method for preparing the multi-coated metal organic framework curcumin microcapsules of the present invention, the concentration of the chitosan solution is 1 to 5 mg / mL.
[0018] As a preferred embodiment of the method for preparing the multi-coated metal organic framework curcumin microcapsules of the present invention, the polysaccharide comprises one of sodium alginate, xanthan gum, gum arabic and konjac gum.
[0019] As a preferred embodiment of the method for preparing the multi-coated metal organic framework curcumin microcapsules of the present invention, the concentration of the polysaccharide solution is 0.5-6 mg / mL.
[0020] As a preferred embodiment of the method for preparing the multi-coated metal organic framework curcumin microcapsules of the present invention, the volume ratio of the chitosan solution to the polysaccharide solution is 0.6-1.1:1.
[0021] Another object of the present invention is to overcome the deficiencies in the prior art and provide a multi-coated metal organic framework curcumin microcapsule.
[0022] Beneficial effects of the present invention:
[0023] The present invention utilizes a solvent thermal synthesis method to prepare a γ-cyclodextrin metal organic framework of uniform size and having a three-dimensional structure, adopts a simple and effective two-step method, utilizes electrostatic deposition to form a chitosan-sodium alginate coating around the curcumin metal organic framework, and prepares a core-shell structure of curcumin multi-coating metal organic framework nanocapsules, which has a simple process and is suitable for industrial production. The chitosan-sodium alginate coating does not affect the encapsulation of curcumin in the metal organic framework, and simultaneously increases the loading capacity of curcumin. In addition, the chitosan-sodium alginate coating prolongs the retention rate of curcumin in different media, enhances the antioxidant properties of curcumin, and improves the stability under ultraviolet irradiation, and the multi-coating metal organic framework microcapsules have the effect of slowly releasing curcumin. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the following briefly introduces the drawings required for describing the embodiments. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative labor. Among them:
[0025] Figure 1 This is a transmission electron micrograph of the curcumin multi-coated metal organic framework curcumin microcapsules in Example 1 of the present invention.
[0026] Figure 2 The particle sizes of the metal organic framework in Example 2 of the present invention under different cyclodextrins are shown.
[0027] Figure 3 The particle sizes of the metal organic framework in Example 3 of the present invention at different molar ratios of γ-cyclodextrin and potassium hydroxide.
[0028] Figure 4 The particle sizes of the metal organic framework in Example 4 of the present invention under different types of surfactants.
[0029] Figure 5 The particle sizes of the metal organic framework in Example 5 of the present invention at different surfactant concentrations.
[0030] Figure 6 The encapsulation efficiency of curcumin of different concentrations in the metal organic framework in Example 6 of the present invention.
[0031] Figure 7 It is the encapsulation efficiency of curcumin in the metal organic framework under different ratios of curcumin to metal organic framework in Example 7 of the present invention.
[0032] Figure 8 The loading conditions of the curcumin multi-coated metal organic framework at different chitosan solution concentrations in Example 8 of the present invention are shown.
[0033] Fig. 9 The loading conditions of the curcumin multi-coated metal organic framework under different types of polysaccharides in Example 9 of the present invention.
[0034] Fig.10 The loading conditions of the curcumin multi-coated metal organic framework at different polysaccharide solution concentrations in Example 10 of the present invention are shown.
[0035] Fig.11 The loading conditions of the curcumin multi-coated metal organic framework in Example 11 of the present invention at different volume ratios of chitosan curcumin metal organic framework solution to polysaccharide solution.
[0036] Fig.12 The loading conditions of curcumin in Control Example 1 and Example 1 of the present invention are shown.
[0037] Fig.13 It is the cumulative release amount of curcumin in different media in Example 1 and Comparative Example 2 of the present invention.
[0038] Fig.14 The anti-ultraviolet oxidation stability of curcumin in Example 1 and Comparative Example 2 of the present invention.
[0039] Fig.15 The stability of curcumin in Example 1 and Comparative Example 3 of the present invention.
[0040] Fig.16 It is the cumulative release amount of curcumin in different media in Example 1 and Comparative Example 3 of the present invention.
[0041] Fig.17 The anti-ultraviolet oxidation stability of curcumin in Example 1 and Comparative Example 3 of the present invention. DETAILED DESCRIPTION
[0042] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the specific implementation methods of the present invention are described in detail below in conjunction with the embodiments of the specification.
[0043] In the following description, many specific details are set forth to facilitate a full understanding of the present invention, but the present invention may also be implemented in other ways different from those described herein, and those skilled in the art may make similar generalizations without violating the connotation of the present invention. Therefore, the present invention is not limited to the specific embodiments disclosed below.
[0044] Secondly, the term "one embodiment" or "embodiment" as used herein refers to a specific feature, structure, or characteristic that may be included in at least one implementation of the present invention. The term "in one embodiment" that appears in different places in this specification does not necessarily refer to the same embodiment, nor does it refer to a separate or selective embodiment that is mutually exclusive with other embodiments.
[0045] Unless otherwise specified, the raw materials used in the present invention are all commercially available.
[0046] Example 1
[0047] This embodiment provides a method for preparing curcumin microcapsules with a multi-coated metal organic framework, specifically:
[0048] 1) dissolving γ-cyclodextrin powder and potassium hydroxide powder in water at a molar ratio of 8:1, and refrigerating at 4° C. for 24 hours for hydration to obtain a reaction solution;
[0049] 2) adding methanol to the reaction solution (reaction solution: methanol = 10:6, v / v) and heating at 60°C for 60 min, adding 6 mg / mL surfactant PEG20000, cooling to 25°C and centrifuging at 5000 g for 5 min at 4°C, washing with methanol and drying under vacuum at 25°C for 24 h to obtain a metal organic framework powder;
[0050] 3) Distributing curcumin powder and metal organic framework powder in an ethanol solution at a mass ratio of 1:1 to make a curcumin concentration of 4 mg / mL, heating and stirring at 40° C. for 4 h, centrifuging, washing the precipitate three times with an ethanol solution, and drying under vacuum at 45° C. to obtain a curcumin metal organic framework powder;
[0051] 4) adding the curcumin metal organic framework powder to a 4 mg / mL chitosan solution and mixing and stirring to obtain a curcumin metal organic framework microcapsule solution coated with chitosan;
[0052] Figure 1 This is a transmission electron micrograph of the curcumin microcapsules with multi-coated metal organic frameworks prepared in Example 1. Figure 1 It can be seen that the curcumin microcapsules coated with multi-metal organic frameworks present a uniformly dispersed spherical shape.
[0053] The kinetic capture of MOFs of a specific size depends on regulating the chemical balance during the preparation stage. This is because these chemical balances determine whether MOFs grow stably toward a bulk phase or are rapidly captured to form nanocrystals. In the solvothermal method, the operating conditions and formulation greatly affect the chemical balance and directly affect the unique properties of MOFs, including crystal size distribution, crystallinity, and crystal morphology. Metal-organic frameworks with smaller particle sizes are more conducive to encapsulating more nutrients. Therefore, it is important to explore the effects of key parameters such as solvent composition and additive concentration on the crystal structure of γ-CD-MOFs.
[0054] Example 2
[0055] This example is used to explore the effects of different cyclodextrin types on the particle size of metal organic frameworks, specifically:
[0056] 1) respectively dissolving α-cyclodextrin, β-cyclodextrin, γ-cyclodextrin powder and potassium hydroxide powder in water at a molar ratio of 8:1, and refrigerating at 4° C. for 24 hours for hydration to obtain a reaction solution;
[0057] 2) adding methanol to the reaction solution (reaction solution: methanol = 10:6, v / v) and heating at 60°C for 60 min, adding 6 mg / mL surfactant PEG20000, cooling to 25°C and centrifuging at 5000 g for 5 min at 4°C, washing with methanol and drying under vacuum at 25°C for 24 h to obtain a metal organic framework powder;
[0058] The particle size of the metal organic framework powder was measured using a laser particle size analyzer. Figure 2 As shown, it can be seen that the particle sizes of the metal organic frameworks prepared by different cyclodextrins are different. When the type of cyclodextrin is γ-cyclodextrin, the particle size of the prepared metal organic framework is the smallest. This is because γ-CD has -OCCO- groups on the primary and secondary surfaces, which can easily form complexes with alkaline metal ions, resulting in a smaller MOF particle size.
[0059] Therefore, gamma-cyclodextrin is preferred as reactant.
[0060] Example 3
[0061] This example is used to explore the effect of different molar ratios of γ-cyclodextrin and potassium hydroxide on the particle size of the metal organic framework, specifically:
[0062] 1) dissolving γ-cyclodextrin powder and potassium hydroxide powder in water at a molar ratio of 9, 8, 7, and 6:1, respectively, and refrigerating at 4° C. for 24 hours for hydration to obtain a reaction solution;
[0063] 2) adding methanol to the reaction solution (reaction solution: methanol = 10:6, v / v) and heating at 60°C for 60 min, adding 6 mg / mL surfactant PEG20000, cooling to 25°C and centrifuging at 5000 g for 5 min at 4°C, washing with methanol and drying under vacuum at 25°C for 24 h to obtain a metal organic framework powder;
[0064] The particle size of the metal organic framework powder was measured using a laser particle size analyzer. Figure 3 As shown, it can be seen that: with the increase of the molar ratio of γ-cyclodextrin and potassium hydroxide, the particle size of the metal organic framework shows a trend of first decreasing and then increasing. When the molar ratio of γ-cyclodextrin and potassium hydroxide is 8:1, the particle size of the prepared metal organic framework is the smallest. This is because under this condition, the two can fully react.
[0065] Taking both cost and particle size into consideration, the molar ratio of γ-cyclodextrin to potassium hydroxide is preferably 8:1 as the optimal reaction molar ratio.
[0066] Example 4
[0067] This example is used to explore the effects of different surfactants on the particle size of metal organic frameworks, specifically:
[0068] 1) dissolving γ-cyclodextrin powder and potassium hydroxide powder in water at a molar ratio of 8:1, and refrigerating at 4° C. for 24 hours for hydration to obtain a reaction solution;
[0069] 2) Methanol was added to the reaction solution (reaction solution: methanol = 10:6, v / v) and heated at 60°C for 60 min. Surfactants PEG200, PEG2000, PEG10000 and PEG20000 were added at a concentration of 6 mg / mL, respectively. After cooling to 25°C, the mixture was centrifuged at 5000 g for 5 min at 4°C. After washing with methanol, the mixture was dried under vacuum at 25°C for 24 h to obtain a metal organic framework powder.
[0070] The particle size of the metal organic framework powder was measured using a laser particle size analyzer. Figure 4 As shown, it can be seen that when PEG20000 is selected as the surfactant, the particle size of the prepared metal organic framework is the smallest, because the molecular weight of PEG20000 is larger, which produces a greater steric hindrance and inhibits the aggregation of particles. Therefore, PEG20000 is preferred as the surfactant.
[0071] Example 5
[0072] This example is used to explore the effect of different surfactant concentrations on the particle size of the metal organic framework, specifically:
[0073] 1) dissolving γ-cyclodextrin powder and potassium hydroxide powder in water at a molar ratio of 8:1, and refrigerating at 4° C. for 24 hours for hydration to obtain a reaction solution;
[0074] 2) Methanol was added to the reaction solution (reaction solution: methanol = 10:6, v / v) and heated at 60°C for 60 min, and surfactant PEG20000 was added at concentrations of 2, 4, 6, 8, and 10 mg / mL, respectively. After cooling to 25°C, the mixture was centrifuged at 5000 g at 4°C for 5 min, washed with methanol, and dried under vacuum at 25°C for 24 h to obtain a metal organic framework powder.
[0075] The particle size of the metal organic framework powder was measured using a laser particle size analyzer. Figure 5 As shown, it can be seen that with the increase of surfactant concentration, the particle size of the metal organic framework shows a trend of first decreasing and then increasing. When the surfactant concentration is 6 mg / mL, the particle size of the prepared metal organic framework is the smallest. This is because this concentration can better inhibit the aggregation of MOF particles and produce a smaller particle size.
[0076] Considering both cost and particle size, 6 mg / mL is preferred as the optimal surfactant concentration.
[0077] As a porous material, cyclodextrin metal organic framework has a large specific surface area and has great potential in the encapsulation and embedding of active ingredients. However, in the process of encapsulating active ingredients in metal organic frameworks, the operating conditions and the concentration of active ingredients greatly affect the encapsulation efficiency. Therefore, it is important to explore the effects of key parameters such as operating conditions and the concentration of active ingredients on the encapsulation efficiency of active ingredients.
[0078] Example 6
[0079] This example is used to explore the effect of different curcumin concentrations on the encapsulation efficiency, specifically:
[0080] 1) dissolving γ-cyclodextrin powder and potassium hydroxide powder in water at a molar ratio of 8:1, and refrigerating at 4° C. for 24 hours for hydration to obtain a reaction solution;
[0081] 2) adding methanol to the reaction solution (reaction solution: methanol = 10:6, v / v) and heating at 60°C for 60 min, adding 6 mg / mL surfactant PEG20000, cooling to 25°C and centrifuging at 5000 g for 5 min at 4°C, washing with methanol and drying under vacuum at 25°C for 24 h to obtain a metal organic framework powder;
[0082] 3) Distributing curcumin powder and metal organic framework powder in an ethanol solution at a mass ratio of 1:1, so that the concentration of curcumin is 2, 4, 6, 8, and 10 mg / mL, respectively, and heating and stirring at 40° C. for 4 h, centrifuging, and washing the precipitate three times with an ethanol solution, and drying under vacuum at 45° C. to obtain curcumin metal organic framework powder.
[0083] The curcumin metal organic framework powder prepared in Example 6 was subjected to the determination of the curcumin encapsulation efficiency, and the determination method was as follows:
[0084] 1) Weigh 1 mg of curcumin metal organic framework powder and dissolve it in anhydrous ethanol solution and dilute to 10 mL to obtain a curcumin metal organic framework standard solution with a mass concentration of 0.1 mg / mL;
[0085] 2) 1, 2, 3, 4, and 5 mL of the curcumin organic framework standard solution were added to a 10 mL volumetric flask, then fixed to volume with anhydrous ethanol, and the absorbance was measured at 420 nm;
[0086] 3) With the concentration of curcumin and the absorbance value as the horizontal and vertical coordinates, the standard curve was obtained: y = 102.32x-82.21, R 2 =0.99; where y is the absorbance value and x is the mass concentration of curcumin (mg / mL);
[0087] 4) Using a spectrophotometer at 420 nm, the absorbance of the supernatant of the ethanol solution containing the curcumin powder and the metal organic framework powder is measured, and the content of the unencapsulated free curcumin is calculated according to the standard curve.
[0088] Encapsulation efficiency of curcumin = (total curcumin content - free curcumin content) / total curcumin content * 100%.
[0089] Attached Figure 6 is the encapsulation efficiency of curcumin at different concentrations in the metal organic framework. Figure 6 It can be seen that as the concentration of curcumin solution increases, the encapsulation rate of curcumin gradually increases, and when the solution concentration is 4 mg / mL, the encapsulation rate of curcumin reaches the maximum value. This is because curcumin is not only encapsulated in the hydrophobic cavity of cyclodextrin, but also in the porous structure of the metal organic framework. When the concentration of curcumin reaches 4 mg / mL, curcumin can be completely encapsulated in the cavity, and the cavity of the metal organic framework is now completely saturated. Further increasing the concentration of curcumin will reduce the encapsulation rate. Considering both cost and encapsulation rate, 4 mg / mL is preferably the optimal solution concentration.
[0090] Example 7
[0091] This example is used to explore the effect of different mass ratios of curcumin powder and metal organic framework powder on the encapsulation efficiency, specifically:
[0092] 1) dissolving γ-cyclodextrin powder and potassium hydroxide powder in water at a molar ratio of 8:1, and refrigerating at 4° C. for 24 hours for hydration to obtain a reaction solution;
[0093] 2) adding methanol to the reaction solution (reaction solution: methanol = 10:6, v / v) and heating at 60°C for 60 min, adding 6 mg / mL surfactant PEG20000, cooling to 25°C and centrifuging at 5000 g for 5 min at 4°C, washing with methanol and drying under vacuum at 25°C for 24 h to obtain a metal organic framework powder;
[0094] 3) Distribute curcumin powder and metal organic framework powder in an ethanol solution at a mass ratio of 0.9, 1, 1.1, 1.2, and 1.3:1, respectively, so that the concentration of curcumin is 4 mg / mL, and heat and stir at 40°C for 4 h, centrifuge, and wash the precipitate three times with ethanol solution, and dry under vacuum at 45°C to obtain curcumin metal organic framework powder.
[0095] The curcumin metal organic framework powder prepared in Example 7 was subjected to the determination of curcumin encapsulation efficiency. The results are shown in the attached figure. Figure 7 As shown, it can be seen that with the increase in the ratio of curcumin to metal organic framework, the encapsulation rate of curcumin gradually increases, and when the mass ratio of the two is 1:1, the encapsulation rate of curcumin reaches the maximum value. This is because when the mass ratio of the two is 1:1, curcumin can be completely encapsulated in all the cavities of the metal organic framework, and when the ratio of the two is further increased, the framework has no more cavities to encapsulate curcumin, thus resulting in a decrease in the encapsulation rate.
[0096] Further increasing the mass ratio of the two did not increase the encapsulation efficiency of curcumin. Considering both cost and encapsulation efficiency, the optimal mass ratio of curcumin to metal organic framework was 1:1.
[0097] Electrostatic coating on the surface of cyclodextrin metal organic framework is an effective strategy to further improve the stability of its encapsulated substances. However, the type of coating greatly affects the loading capacity of the encapsulated active ingredients. Therefore, it is important to explore the effects of key parameters such as operating conditions and coating type and concentration on the loading capacity of active ingredients.
[0098] Example 8
[0099] This example is used to explore the effect of different chitosan solution concentrations on curcumin loading, specifically,
[0100] 1) dissolving γ-cyclodextrin powder and potassium hydroxide powder in water at a molar ratio of 8:1, and refrigerating at 4° C. for 24 hours for hydration to obtain a reaction solution;
[0101] 2) adding methanol to the reaction solution (reaction solution: methanol = 10:6, v / v) and heating at 60°C for 60 min, adding 6 mg / mL surfactant PEG20000, cooling to 25°C and centrifuging at 5000 g for 5 min at 4°C, washing with methanol and drying under vacuum at 25°C for 24 h to obtain a metal organic framework powder;
[0102] 3) Distributing curcumin powder and metal organic framework powder in an ethanol solution at a mass ratio of 1:1 to a curcumin concentration of 4 mg / mL, heating and stirring at 40° C. for 4 h, centrifuging, washing the precipitate three times with an ethanol solution, and drying under vacuum at 45° C. to obtain a curcumin metal organic framework powder;
[0103] 4) adding the curcumin metal organic framework powder to 1, 2, 4, 6, and 8 mg / mL chitosan solutions respectively, and mixing and stirring to obtain a curcumin metal organic framework microcapsule solution coated with chitosan;
[0104] 5) The curcumin metal organic framework microcapsule solution coated with chitosan was added to a 2 mg / mL sodium alginate solution at a volume ratio of 0.9:1, centrifuged, and the precipitate was washed three times with an ethanol solution, and dried under vacuum at 45° C. to obtain multi-coated metal organic framework curcumin microcapsules.
[0105] The curcumin loading of the multi-coated metal organic framework curcumin microcapsules obtained in Example 8 was measured:
[0106] Curcumin loading = (total curcumin content - free curcumin content) / microcapsule mass * 100%.
[0107] Attached Figure 8 The curcumin microcapsule loading of multi-coated metal organic framework at different chitosan solution concentrations. It can be seen that with the increase of chitosan solution concentration, the curcumin loading gradually increases. When the concentration is 4 mg / mL, the curcumin loading reaches the maximum value. This is because further increasing the chitosan concentration will lead to a decrease in the proportion of curcumin, resulting in a decrease in its loading capacity.
[0108] Example 9
[0109] This example is used to explore the effects of different polysaccharide types on curcumin loading, specifically,
[0110] 1) dissolving γ-cyclodextrin powder and potassium hydroxide powder in water at a molar ratio of 8:1, and refrigerating at 4° C. for 24 hours for hydration to obtain a reaction solution;
[0111] 2) adding methanol to the reaction solution (reaction solution: methanol = 10:6, v / v) and heating at 60°C for 60 min, adding 6 mg / mL surfactant PEG20000, cooling to 25°C and centrifuging at 5000 g for 5 min at 4°C, washing with methanol and drying under vacuum at 25°C for 24 h to obtain a metal organic framework powder;
[0112] 3) Distributing curcumin powder and metal organic framework powder in an ethanol solution at a mass ratio of 1:1 to a curcumin concentration of 4 mg / mL, heating and stirring at 40° C. for 4 h, centrifuging, washing the precipitate three times with an ethanol solution, and drying under vacuum at 45° C. to obtain a curcumin metal organic framework powder;
[0113] 4) adding the curcumin metal organic framework powder to 4 mg / mL chitosan solution and mixing and stirring to obtain a curcumin metal organic framework microcapsule solution coated with chitosan;
[0114] 5) The chitosan-coated curcumin metal organic framework microcapsule solution was added to 2 mg / mL sodium alginate, xanthan gum, gum arabic, and konjac gum solutions at a volume ratio of 0.9:1, respectively, and the mixture was centrifuged, and the precipitate was washed three times with an ethanol solution, and dried under vacuum at 45° C. to obtain multi-coated metal organic framework curcumin microcapsules.
[0115] The curcumin loading of the multi-coated metal organic framework curcumin microcapsules obtained in Example 9 was measured. The results are shown in the attached Fig. 9 As shown, it can be seen that different types of polysaccharides also affect the loading capacity of curcumin. When the polysaccharide is sodium alginate, the loading capacity of curcumin reaches the maximum value. This is because the electrostatic interaction between sodium alginate and chitosan is stronger, which can prevent the loss of curcumin during the encapsulation process and increase its loading capacity.
[0116] Example 10
[0117] This example is used to explore the effect of different polysaccharide solution concentrations on curcumin loading, specifically,
[0118] 1) dissolving γ-cyclodextrin powder and potassium hydroxide powder in water at a molar ratio of 8:1, and refrigerating at 4° C. for 24 hours for hydration to obtain a reaction solution;
[0119] 2) adding methanol to the reaction solution (reaction solution: methanol = 10:6, v / v) and heating at 60°C for 60 min, adding 6 mg / mL surfactant PEG20000, cooling to 25°C and centrifuging at 5000 g for 5 min at 4°C, washing with methanol and drying under vacuum at 25°C for 24 h to obtain a metal organic framework powder;
[0120] 3) Distributing curcumin powder and metal organic framework powder in an ethanol solution at a mass ratio of 1:1 to a curcumin concentration of 4 mg / mL, heating and stirring at 40° C. for 4 h, centrifuging, washing the precipitate three times with an ethanol solution, and drying under vacuum at 45° C. to obtain a curcumin metal organic framework powder;
[0121] 4) adding the curcumin metal organic framework powder to 4 mg / mL chitosan solution and mixing and stirring to obtain a curcumin metal organic framework microcapsule solution coated with chitosan;
[0122] 5) The chitosan-coated curcumin metal organic framework microcapsule solution was added to 0.5, 1, 2, 4, and 6 mg / mL sodium alginate solutions at a volume ratio of 0.9:1, respectively, and the mixture was centrifuged, and the precipitate was washed three times with an ethanol solution, and dried under vacuum at 45° C. to obtain multi-coated metal organic framework curcumin microcapsules.
[0123] The curcumin loading of the multi-coated metal organic framework curcumin microcapsules obtained in Example 10 was measured. The results are shown in the attached Fig.10 As shown, it can be seen that with the increase of the concentration of sodium alginate solution, the loading capacity of curcumin gradually increases, and when the concentration is 2 mg / mL, the loading capacity of curcumin reaches the maximum value. Further increasing the concentration of sodium alginate solution does not increase the loading capacity of curcumin, because further increasing the concentration of sodium alginate leads to a decrease in the proportion of curcumin, which is not conducive to the increase of its loading capacity.
[0124] Embodiment 11
[0125] This example is used to explore the effect of different volume ratios of chitosan and sodium alginate on the curcumin loading, specifically,
[0126] 1) dissolving γ-cyclodextrin powder and potassium hydroxide powder in water at a molar ratio of 8:1, and refrigerating at 4° C. for 24 hours for hydration to obtain a reaction solution;
[0127] 2) adding methanol to the reaction solution (reaction solution: methanol = 10:6, v / v) and heating at 60°C for 60 min, adding 6 mg / mL surfactant PEG20000, cooling to 25°C and centrifuging at 5000 g for 5 min at 4°C, washing with methanol and drying under vacuum at 25°C for 24 h to obtain a metal organic framework powder;
[0128] 3) Distributing curcumin powder and metal organic framework powder in an ethanol solution at a mass ratio of 1:1 to a curcumin concentration of 4 mg / mL, heating and stirring at 40° C. for 4 h, centrifuging, washing the precipitate three times with an ethanol solution, and drying under vacuum at 45° C. to obtain a curcumin metal organic framework powder;
[0129] 4) adding the curcumin metal organic framework powder to 4 mg / mL chitosan solution and mixing and stirring to obtain a curcumin metal organic framework microcapsule solution coated with chitosan;
[0130] 5) The curcumin metal organic framework microcapsule solution coated with chitosan was added to a 2 mg / mL sodium alginate solution at a volume ratio of 0.6, 0.7, 0.8, 0.9, 1.0, and 1.1:1, respectively, and the mixture was centrifuged, and the precipitate was washed three times with an ethanol solution and dried under vacuum at 45° C. to obtain multi-coated metal organic framework curcumin microcapsules.
[0131] The curcumin loading of the multi-coated metal organic framework curcumin microcapsules obtained in Example 11 was measured. The results are shown in the attached Fig.11 As shown, it can be seen that with the increase of the volume ratio of chitosan to sodium alginate solution, the loading capacity of curcumin gradually increases. When the ratio between the two is 0.9:1, the loading capacity of curcumin reaches the maximum value. This is because at this ratio, the two can be better combined through electrostatic interaction, preventing the leakage of curcumin in the metal skeleton and increasing its loading capacity.
[0132] Comparative Example 1
[0133] Comparative Example 1 provides pure curcumin powder purchased from Shanghai MacLean Biochemical Technology Co., Ltd. (purity 98%, analytical grade).
[0134] Comparative Example 2
[0135] Comparative Example 2 is based on Example 1. The difference between Comparative Example 2 and Example 1 is that no sodium alginate solution is added. Specifically:
[0136] 1) dissolving γ-cyclodextrin powder and potassium hydroxide powder in water at a molar ratio of 8:1, and refrigerating at 4° C. for 24 hours for hydration to obtain a reaction solution;
[0137] 2) adding methanol to the reaction solution (reaction solution: methanol = 10:6, v / v) and heating at 60°C for 60 min, adding 6 mg / mL surfactant PEG20000, cooling to 25°C and centrifuging at 5000 g for 5 min at 4°C, washing with methanol and drying under vacuum at 45°C for 24 h to obtain a metal organic framework powder;
[0138] 3) Distributing curcumin powder and metal organic framework powder in an ethanol solution at a mass ratio of 1:1 to make a curcumin concentration of 4 mg / mL, heating and stirring at 40° C. for 4 h, centrifuging, washing the precipitate three times with an ethanol solution, and drying under vacuum at 45° C. to obtain a curcumin metal organic framework powder;
[0139] 4) adding the curcumin metal organic framework powder to a 4 mg / mL chitosan solution and mixing and stirring to obtain a curcumin metal organic framework microcapsule solution coated with chitosan;
[0140] 5) The curcumin metal organic framework microcapsule solution coated with chitosan was centrifuged, and the precipitate was washed three times with an ethanol solution, and dried under vacuum at 45° C. to obtain a curcumin-chitosan single-coated metal organic framework microcapsule powder.
[0141] The prepared curcumin metal organic framework microcapsule powder was subjected to the determination of curcumin loading, and the determination method was as follows:
[0142] (1) Drawing of curcumin standard curve
[0143] Accurately weigh 1 mg of curcumin standard, dissolve it in anhydrous ethanol solution and dilute to 10 mL to obtain a curcumin standard solution with a mass concentration of 0.1 mg / mL. Accurately pipette 1, 2, 3, 4, and 5 mL of curcumin standard solution into a 10 mL volumetric flask, then dilute with anhydrous ethanol and measure its absorbance at 420 nm. Use curcumin concentration and absorbance as the horizontal and vertical coordinates, respectively, to obtain a standard curve: y = 102.32x-82.21, R 2 =0.99; wherein y is the absorbance value and x is the mass concentration of curcumin (mg / mL).
[0144] (2) Determination of curcumin stability
[0145] The metal organic framework loaded with 4 mg of curcumin was dissolved in ethanol, then diluted with water or ethanol to a final concentration of 14 μM curcumin and placed in the dark. The stability of curcumin in aqueous and ethanol solutions was measured by a visible spectrophotometer at different time intervals of 0 to 12 h. The data were recorded in Fig.12 In. From Fig.12 It can be seen that the stability of curcumin in chitosan single-coated metal-organic frameworks is significantly lower than that in multi-coated metal-organic frameworks.
[0146] (3) Cumulative release in different media
[0147] The metal organic framework loaded with 4 mg of curcumin was dispersed in 10 mL of release medium and then placed in a dialysis bag (dialysis bag molecular weight cutoff, 10 kDa), and 150 mL of different media (HCl solution with pH = 1.2, phosphate buffer with pH = 6.8) were added around to simulate different physiological pH conditions. In order to release curcumin more evenly in the medium, 20% ethanol was added to the simulated medium and magnetic stirring was performed at 37°C. At a predetermined time point (0 to 24 h), the amount of curcumin released in the two different media was measured by UV-visible spectroscopy at 420 nm. The results are shown in the attached figure. Fig.13 shown.
[0148] from Fig.13 It can be seen that compared with the chitosan single-coated metal organic framework, the multi-coated metal organic framework loaded with curcumin has the ability to slowly release, which is mainly attributed to the formation of its dense structure, thereby limiting the medium diffusion capacity of curcumin. This result shows that the multi-coated metal organic framework can be used as an effective delivery carrier for the controlled release of curcumin.
[0149] (4) Anti-ultraviolet oxidation stability
[0150] In order to investigate the antioxidant stability of γ-cyclodextrin loaded with curcumin, the DPPH free radical scavenging activity of γ-cyclodextrin powder loaded with curcumin was measured after irradiation with 20W UV lamp for 30min, and the data were recorded in Fig.14 middle. Fig.14 It can be seen that curcumin is encapsulated in a multi-coated metal-organic framework, which significantly improves its antioxidant stability. This is because the surface coating blocks the speed at which ultraviolet rays reach the interior, thereby improving the stability of curcumin.
[0151] Comparative Example 3
[0152] Electrostatic coating on the surface of cyclodextrin metal organic frameworks is an effective strategy to further improve the stability of its encapsulated substances. However, the type of coating greatly affects the physicochemical stability of the encapsulated active ingredients. Therefore, it is important to explore the protective properties of different coatings on active ingredients.
[0153] This comparative example is used to explore the effects of different coatings on the physicochemical stability of curcumin, specifically,
[0154] The stability, release, free radical scavenging ability and anti-ultraviolet oxidation stability of metal organic frameworks with different coatings containing the same curcumin loading were determined by the following method:
[0155] (1) Drawing of curcumin standard curve
[0156] Accurately weigh 1 mg of curcumin standard, dissolve it in anhydrous ethanol solution and dilute to 10 mL to obtain a curcumin standard solution with a mass concentration of 0.1 mg / mL. Accurately pipette 1, 2, 3, 4, and 5 mL of curcumin standard solution into a 10 mL volumetric flask, then dilute with anhydrous ethanol and measure its absorbance at 420 nm. Use curcumin concentration and absorbance as the horizontal and vertical coordinates, respectively, to obtain a standard curve: y = 102.32x-82.21, R 2 =0.99; wherein y is the absorbance value and x is the mass concentration of curcumin (mg / mL).
[0157] (2) Determination of curcumin stability
[0158] Different coated metal organic frameworks loaded with 4 mg of curcumin were dissolved in ethanol, then diluted with water or ethanol to a final concentration of 14 μM curcumin and placed in the dark. The stability of curcumin in aqueous and ethanol solutions was measured by visible spectrophotometer at different time intervals of 0 to 12 h. The data were recorded in Fig.15 In. From Fig.15 It can be seen that curcumin has the highest stability in the metal-organic frameworks with added chitosan and sodium alginate coatings.
[0159] (4) Cumulative release in different media
[0160] The metal organic frameworks with different coatings loaded with 4 mg of curcumin were dispersed in 10 mL of release medium and then placed in a dialysis bag (dialysis bag molecular weight cutoff, 10 kDa), and 150 mL of different media (HCl solution with pH = 1.2, phosphate buffer with pH = 6.8) were added around to simulate different physiological pH conditions. In order to make curcumin more evenly released in the medium, 20% ethanol was added to the simulated medium and magnetically stirred at 37°C. At predetermined time points (0 to 24 h), the amount of curcumin released in the two different media was measured by UV-visible spectroscopy at 420 nm, and the data were recorded in Fig.16 middle.
[0161] from Fig.16 It can be seen that the metal organic framework with chitosan and sodium alginate coating has the ability of slow release, which is mainly attributed to the denser structure of chitosan and sodium alginate, thus limiting the medium diffusion capacity of curcumin. This result shows that the metal organic framework with chitosan and sodium alginate coating can be used as an effective delivery carrier for the controlled release of curcumin.
[0162] (6) Anti-ultraviolet oxidation stability
[0163] In order to investigate the antioxidant stability of curcumin-loaded metal organic frameworks with different coatings, the DPPH radical scavenging activity of curcumin-loaded metal organic frameworks with different coatings was measured after irradiation with 20W UV light for 30min, and the data were recorded in Fig.17 middle. Fig.17 It can be seen that curcumin is encapsulated in a metal organic framework with chitosan and sodium alginate coating, which significantly improves its antioxidant stability. This may be because the combination of chitosan and sodium alginate is more conducive to resisting ultraviolet rays, thereby improving the stability of curcumin.
[0164] Our invention uses electrostatic deposition to form a chitosan-sodium alginate coating around the curcumin metal organic framework to prepare a core-shell structured curcumin multi-coated metal organic framework nanocapsule, which has a simple process and is suitable for industrial production. The chitosan-sodium alginate coating does not affect the encapsulation of curcumin in the metal organic framework, while increasing the loading capacity of curcumin. In addition, the chitosan-sodium alginate coating prolongs the retention rate of curcumin in different media, enhances the antioxidant properties of curcumin, and improves the stability under ultraviolet irradiation. At the same time, the multi-coated metal organic framework microcapsule has the effect of slowly releasing curcumin.
[0165] It should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solutions of the present invention may be modified or replaced by equivalents without departing from the spirit and scope of the technical solutions of the present invention, which should all be included in the scope of the claims of the present invention.
Claims
1. A method for preparing a multi-coated metal organic framework curcumin microcapsule, characterized in that: include, Dissolving cyclodextrin powder and potassium hydroxide powder in water at a molar ratio of 6 to 9:1, hydrating after refrigeration to obtain a reaction solution; Methanol is added to the reaction solution and heated, then a surfactant is added, the solution is cooled and centrifuged, and the solution is washed with methanol and freeze-dried to obtain a metal organic framework powder; Adding metal organic framework powder and curcumin powder together into an ethanol solution at a mass ratio of 1:0.7-1.1, washing the precipitate three times with the ethanol solution after centrifugation, and vacuum drying to obtain curcumin metal organic framework powder; Adding curcumin metal organic framework powder to chitosan solution and mixing and stirring to obtain a curcumin metal organic framework microcapsule solution coated with chitosan; The curcumin metal organic framework microcapsule solution coated with chitosan is added to the polysaccharide solution, and the precipitate is washed three times with an ethanol solution after centrifugation, and vacuum dried to obtain the curcumin microcapsules with multiple coating metal organic frameworks; Wherein, the volume ratio of the chitosan solution to the polysaccharide solution is 0.6-1.1:1; The cyclodextrin is one of α-cyclodextrin, β-cyclodextrin and γ-cyclodextrin; The surfactant is one of PEG200, PEG2000, PEG10000 and PEG20000; The polysaccharide is sodium alginate.
2. The method for preparing curcumin microcapsules with multi-coated metal organic frameworks according to claim 1, characterized in that: The molar ratio of the cyclodextrin to potassium hydroxide is 7-8:
1.
3. The method for preparing curcumin microcapsules with multi-coated metal organic framework according to claim 1 or 2, characterized in that: The concentration of the surfactant is 2-10 mg / mL.
4. The method for preparing curcumin microcapsules with multi-coated metal organic frameworks according to claim 1, characterized in that: The concentration of the curcumin is 2-10 mg / mL.
5. The method for preparing curcumin microcapsules with multi-coated metal organic frameworks according to claim 1 or 4, characterized in that: The mass ratio of the curcumin powder to the metal organic framework powder is 0.8-1:
1.
6. The method for preparing curcumin microcapsules with multi-coated metal organic frameworks according to claim 1, characterized in that: The concentration of the chitosan solution is 1-5 mg / mL.
7. The method for preparing curcumin microcapsules with multi-coated metal organic frameworks according to claim 1, characterized in that: The concentration of the polysaccharide solution is 0.5-6 mg / mL.
8. Curcumin microcapsules with multi-coating metal organic frameworks prepared according to the preparation method described in any one of claims 1 to 7.
Citation Information
Patent Citations
Preparation method of resveratrol microcapsule based on metal organic framework
CN116327737A